A systematic review and modeling of the effect of bacteriophages on Salmonella spp. Reduction in chicken meat. Issue 4 (April 2023) - Shahdadi, Mohsen; Safarirad, Maryam; Berizi, Enayat; Mazloomi, Seyed Mohammad; Hosseinzadeh, Saeid; Zare, Morteza; Derakhshan, Zahra; Rajabi, Saeed
Abstract: Prevention and control of foodborne pathogens are of vital public health importance, and poultry meat is recognized as a major source of Salmonella infection in humans. Therefore, it is necessary to reduce the presence of salmonella in poultry meat. This article provided a systematic review and modeling to assess the effect of various factors on bacteriophages' function on Salmonella spp. Reduction in poultry meat. Twenty-two studies were included based on the inclusion and exclusion criteria mentioned in the methodology. The results showed that each unit increase in bacterial dose, phage dose, and temperature increases the Salmonella reduction by about 7%, 20%, and 1%, respectively. In addition, wild-type phages were more efficient than commercial-type phages, and this result was statistically significant (β = 1.124; p-value <0.001). This multivariate analysis is a helpful tool to predict the role of various factors in the role of phage in reducing Salmonella in poultry meat.